The Influence Of Organizational Culture And Work Discipline On Employee Performance At PT. Korda Anak Sapek - Sonya S Wulandari (CV. HEI PUBLISHING INDONESIA, 2024)
The purpose of this study is to ascertain how work discipline and organizational culture affect employee performance. This study employs a quantitative approach with a sample size of 35 employees from PT. Korda Anak Sapek as the object of the investigation. Saturated samples are used in the sampling process, and statistical hypothesis testing, multiple linear regression analysis, validity testing, reliability testing, and testing of classical assumptions are among the data analysis techniques used. The study's findings indicate that work discipline and organizational culture both have a partial impact on employee performance, that these two factors have an impact on performance simultaneously, and that both work discipline and organizational culture have an impact on performance